Safety analysis of the modified method of collecting nasopharyngeal swab samples in COVID-19 screening (新型冠状病毒肺炎筛查鼻咽拭子标本采集安全性方法的研究) - LI Na (李娜); LIU Suyan (刘素彦) (中西医结合护理)
Objective To explore the safety of the modified method of collecting nasopharyngeal swab samples in COVID-19 screening. Methods A cross-sectional study was conducted. Totally 430 nasopharyngeal swab samples were collected from participants by using routine collecting method. Another 406 samples were collected from participants by using modified collecting method: before collecting the nasopharyngeal swab sample, participant’s nasal cavity was cleaned with 0. 9% normal saline, and psychological nursing interventions were carried out during the period of samples collecting. Results The modified method was associated with lower incidence rates of pain in nasal cavity, cough and sneezing(P<0. 05). Conclusion In order to reduce the symptoms of nasal pain, coughing and sneezing, more attention should be paid to psychological guidance and taking effective intervention in the collection of nasopharyngeal swab samples. It can not only improve the comfort of the subjects, but also reduce the risk of infection among sample collection personnel, and effectively improve the collection safety. (目的 探讨新型冠状病毒肺炎筛查鼻咽拭子标本采集改进方法的安全性及舒适度。方法 采用横断面描述性研究方法。2020年11月对430例被采集者采用常规方法进行鼻咽拭子标本采集; 12月对406例被采集者采用改进方法进行鼻咽拭子标本采集, 即在标本采集前使用0. 9%生理盐水充分清理鼻腔, 增加鼻前庭的湿润度, 同时在操作前和操作中加强心理指导。结果 改进采集方法后, 采集中出现鼻腔疼痛、咳嗽、打喷嚏症状的比例较改进前降低, 差异有统计学意义(P<0. 05)。结论 在常规鼻咽拭子采集方法的基础上, 加强心理指导和采取有效干预措施, 可减少采集过程中出现的鼻腔疼痛、咳嗽和打喷嚏症状, 不仅可以提高被采集者舒适度, 同时也减少采集人员被感染的风险。)